The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.3109/07435800009066177
|View full text |Cite
|
Sign up to set email alerts
|

Transient Neonatal Hypothyroidism Alters Plasma and Testicular Sex Steroid Concentration in Puberal Rats

Abstract: The stimulatory and inhibitory effects on testicular steroidogenesis of transient neonatal hypothyroidism from day 1 postpartum through different postnatal developmental events on testis at puberal age (60 days old) were studied in vivo. Hypothyroidism was induced in neonates by feeding the lactating mother or directly with 0.05% methimazole (MMI) through drinking water from the day of parturition to 10, 15, 30, 40 and 60 days, and were killed at day 60 postpartum. Plasma and testicular interstitial fluid (TIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Our earlier study on this condition suggested that plasma and TIF progesterone levels were decreased and T and DHT levels were initially unaltered but decreased with increasing duration of hypothyroidism. TIF E2 levels were increased in transient neonatal hypothyroid rats by the time they reached pubertal age [66].…”
Section: Serum Sex Steroids Under Altered Thyroid Statusmentioning
confidence: 93%
See 1 more Smart Citation
“…Our earlier study on this condition suggested that plasma and TIF progesterone levels were decreased and T and DHT levels were initially unaltered but decreased with increasing duration of hypothyroidism. TIF E2 levels were increased in transient neonatal hypothyroid rats by the time they reached pubertal age [66].…”
Section: Serum Sex Steroids Under Altered Thyroid Statusmentioning
confidence: 93%
“…In the late 1970s, Amin and El-Sheikh [3] reported the presence of numerous well-developed interstitial cells in hyperthyroid rats while the opposite was found for hypothyroid rats. Transient neonatal hypothyroidism resulted in 70% increase in number and labeling index of Leydig cells, and their volume declined by 20% [38,39,66,73]. Recent studies showed that neonatal hypothyroidism decreased the Leydig cell number and increased the mesenchymal=peritubular cells.…”
Section: Thyroid Hormones and Leydig Cell Numbermentioning
confidence: 99%
“…As a consequence of the increased number of precursor mesenchymal cells accumulated in the testicular interstitium, a significant increase in the size of the adult Leydig cell population was observed in the adult testis when euthyroidism was restored (Maran et al, 2000;Mendis-Handagama and Ariyaratne, 2004). On the other hand, neonatal-prepubertal hyperthyroidism was shown to stimulate the onset of Leydig cell differentiation by increasing the number of mesenchymal cells produced and recruited into the differentiation pool to increase the number of differentiated Leydig cells in the prepubertal period (Ariyaratne et al, 2000a,b;Mendis-Handagama and Ariyaratne, 2001;Teerds et al, 1998).…”
Section: Actions Of Thyroid Hormone On Testismentioning
confidence: 98%
“…However, hypothyroidism is a complex hormonal dysfunction that has been associated with reduced secretion of gonadotropin-realizing hormones, FSH, LH, and testosterone (Antony et al, 1995;Chandrasekhar et al, 1986;Chiao et al, 1999;Jannini et al, 1995;Kirby et al, 1997;Maran et al, 2000;Ruiz et al, 1989). Moreover, systemic hormones are the first step regulators of spermatogenesis while paracrine and autocrine factors synthesized by testicular cells are also involved in local control of germ cell development (de Kretser et al, 1998;Sofikitis et al, 2008).…”
Section: Thyroid Hormone and The Adult Testismentioning
confidence: 99%
“…They revealed that exposing rats to carbimazole caused different histological changes included blood vessels congestion, hemorrhage, damage of interstitium and the spermatogenic cells showed apoptosis and necrosis. Maran et al [25] recorded reduction of testes weight, decrease of leydig cell number and diameter, and reduction of peritubular myoid cell number after administration of methimazole to immature rats. Okdah [26] reported that methimazole caused significant decrease in diameter of seminiferous tubules and inhibition of spermatogenesis in rats.…”
Section: Discussionmentioning
confidence: 99%